101+ careers in gerontology - Grabinski, C. Joanne, 1941- (Springer Publishing Company, 2015)
Describes a wealth of diverse employment opportunities in gerontology and how to land them. How do you know if a career in gerontology is right for you? What opportunities exist in the field? Completely updated to reflect significant changes to policy and management of resources, the second edition of 101 Careers in Gerontology provides a wealth of helpful and timely guidance in this rapidly growing field. Written for all levels of job seekers ranging from community college students to credential-seeking professionals, the book outlines a multitude of opportunities that dovetail with careers r.